How do care home staff understand, manage and respond to agitation in people with dementia? A qualitative study. Issue 6 (30th June 2018) - Rapaport, Penny; Livingston, Gill; Hamilton, Olivia; Turner, Rebecca; Stringer, Aisling; Robertson, Sarah; Cooper, Claudia
Abstract : Objectives: Little is known about how care home staff understand and respond to distress in residents living with dementia labelled as agitation. The aim of this study was to describe how care home staff understand and respond to agitation and the factors that determine how it is managed. Design: We conducted a qualitative thematic analysis. Setting: We recruited staff from six care homes in South East England including residential and nursing homes of differing sizes run by both the private and charity sector and located in urban and rural areas. Participants: We interviewed 25 care home staff using purposive sampling to include staff of either sex, differing age, ethnicity, nationality and with different roles and experience. Results: We identified four overarching themes: (1) behaviours expressing unmet need; (2) staff emotional responses to agitation; (3) understanding the individual helps and (4) constraints on staff responses. Staff struggled with the paradox of trying to connect with the personhood of residents while seeing the person as separate to and, therefore, not responsible for their behaviours. Staff often felt powerless, frightened and overwhelmed, and their responses were constrained by care home structures, processes and a culture of fear and scrutiny. Conclusions: Responding to agitation expressed by residents was not a linear process and staff faced tensions and dilemmas in deciding how to respond, especially when initial strategies were unsuccessful or when attempts to respond to residents' needs were inhibited by structural and procedural constraints in the care home. Future trials of psychosocial interventions should support staff to identify and respond to residents' unmet needs and include how staff can look after themselves.